Perceptions Regarding Online Nursing Education Among Students in College of Nursing – Umm Al Qura University, Makkah, Saudi Arabia - Alamry, Nora; Almoteri, Nada; Bagadood, May H.; Alghabbashi, Maram T. (British Journal of Healthcare and Medical Research, 2023)
Background: The common ways of providing education to students, online learning, blended learning, flipped learning, tutorials, and seminars. Aim: This study aimed to assess the perception of nursing students toward online learning during theCOVID‐19 pandemic. Methodology: A descriptive cross-sectional research design was used on 136 nursing students were selected conveniently. Results: There is appositive statistically significant correlation were years of study, age, and advantage of online education only in the items related to supportive, easily understood, availability, improved abilities, and feedback. Conclusion and Recommendations: There is a growing demand for strategies that take into consideration all the needs of nursing students toward online learning and formulating curricula that improving online educational environment and outcomes.